Performance of concrete made with commercially produced recycled coarse and fine aggregates in the Cape Peninsula - Kutegeza, Benjamin (Department of Mechanical Engineering, 2024)
[pg129,130 missing] Properties and performance of concrete made with laboratory-crushed recycled aggregate have been extensively investigated and reported by various researchers. However, only limited data are available on commercially produced recycled aggregates (RA). In this study, the properties of RA and the performance of concrete made with RA were analysed and compared with the properties of natural aggregate and normal concrete respectively. The results obtained from this study show the material to be within allowable limits suggested by various concrete Standards and specifications. Both recycled coarse aggregate (RCA) and fine aggregate (RFA) were continuously graded. Stone content was the main component in the RA, with mass fraction of about 58%. Stone/mortar conglomerate (concrete) comprised about 21 %, mortar comprised 12% and bricks comprised 8%. Other impurities such as wood, chipboards, and tiles to mention a few totalled about 1 %.